2001
DOI: 10.1046/j.0960-7722.2001.00208.x
|View full text |Cite
|
Sign up to set email alerts
|

p21WAF1 is associated with CDK2 and CDK4 protein during HL‐60 cell differentiation by TPA treatment

Abstract: TPA-treated HL-60 cells are mainly arrested in G1 by p21(WAF1) accumulation. We investigate the downstream changes following such accumulation. Increased p21(WAF1) is associated with CDK2 and CDK4. pRb is dephosphorylated in the presence of p21-CDK2/4 complexes, and the Rb-E2F1 complex increases after TPA treatment, whereas the Rb-HDAC1 complex decreases slightly. Our results suggest that increased p21(WAF1) is associated with CDK2/4, and that these complexes induce pRb dephosphorylation. In turn, hypophosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Waf1/Cip1 and p27 Kip1 , resulting in Cdk2 kinase activity inhibition [51][52][53][54][55][56]. Therefore, in order to characterize the molecular pathway by which LRRC4 mediates its antiproliferative action upon the U251MG cell line, a complete analysis of the cell cycle events in these cells both prior to and consequent of the initial observed G1 arrest at 36 h was performed (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Waf1/Cip1 and p27 Kip1 , resulting in Cdk2 kinase activity inhibition [51][52][53][54][55][56]. Therefore, in order to characterize the molecular pathway by which LRRC4 mediates its antiproliferative action upon the U251MG cell line, a complete analysis of the cell cycle events in these cells both prior to and consequent of the initial observed G1 arrest at 36 h was performed (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The induction of p21, a CDK inhibitor, is responsible for arresting cell cycle progression via p53-dependent and -independent pathways (Gartel, 2005). Decreased CDK4 expression and increased p21 WAF1 expression were associated with cell cycle arrest (Cho et al, 2001;Sherr et al, 2002). Moreover, a mitogen-activated protein kinase (MAPK) or extracellular signal-regulated kinase 1/2 (ERK1/2) signaling cascade is of great importance in regulating various cellular responses, including proliferation, differentiation, survival, and cell death.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in p21 in TPA treated HL-60 cells was earlier observed by immunoblotting. 38 In summary, it appears that the more rapid cessation of cell division seen with TPA treated cells, compared with RA treated cells, may result from a faster reduction of CDK and cyclin transcripts and a significant inhibition of the protein complexes needed for cell cycle progression.…”
Section: Cell Cyclementioning
confidence: 99%
“…The mechanism of cell death in TPA treated HL-60 cells is somewhat more complex. 38,42 These studies demonstrated that a small fraction (»10%) of the HL-60 cells do not differentiate after the addition of TPA, do not attach and do undergo apoptosis. The attached cells, which are overwhelmingly stopped in G1 phase, remain alive.…”
Section: Apoptosismentioning
confidence: 99%